Concreto sobre areia e sal: A (re)invenção da Comunidade de Caraguatatuba/SP (1950-2010) – Territórios e Identidades, Transformações e Permanências - Fonseca, Alex Sandro Santos [UNIFESP] (2016)
The conception of Caiçara culture - the lifeways of beachcombers and watermen - suffered importants transformations during twentieth century. Those changes affected the relationship between the traditional communities and public authorities and, in this sense, the way these communities were contemplated in public policy over time. Those changes of conception also guided the production of different narratives of Caiçara culture, in the wake of these changes the Caiçara community of Camaroeiro in Caraguatatuba, São Paulo, Brazil, faced the appropriation of their territory and their culture, at the same time experiencing the decline of their customs and traditions. This research seeks to analyze the trajectory of this community through different narratives and temporalities, temporalities that were marked by intense deterritorialization processes and the repossession of Camaroeiro Community. Parallel to these structural and material changes, the thesis also sought to chartchanges of perspective in relation to the community?s role and centrality in policies of tourism, culture and heritage. To accomplish these objectives, the project articulated theoretical and methodological approaches from History, Geography and other social sciences producing aninterdisciplinary analysis of the development of different narratives about Caiçara culture and the Camaroeiro Community of Caraguatatuba between the 1950s and 2010.